Differentiated Competence mampu meningkatkan Kinerja Dosen di era Teknologi Informasi yg dimediasi oleh Employee Engagement - Agus Hilman Tuarita; Siwi Dyah Ratnasari (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The purpose of this stud research is to determine the effect of 1) Differentiated Competence on teaching staff (lecturers) performance in the digitalization era. 2) Differentiated Competence towards employee engagement in the digitalization era. 3) Employee Engagement on lecturer performance in the digitalization era. 4) Differentiated Competence on lecturer performance mediated by Employee Engagement in the digitalization era. This type of research is explanatory. The population of the research is universities (PT) in Malang with an accounting study program accredited A. The sample was taken randomly from 4 universities in Malang, namely Brawijaya University, UIN Malang, Widya Gama University, and STIE Malangkucecwara, with a total sample of 105 lecturers. SMART PLS was used to evaluate the data. The study results reveal that 1) Differentiated Competence affects lecturer performance. 2) Differentiated CompetencyCompetency affects Employee Engagement 3) Differentiated Competency affects higher Employee Engagement 4) Differentiated Competency positively and significantly influences lecturer performance through Employee Engagement. The learning process can no longer use the old pattern. Lecturers must keep up with technological developments to produce highly competitive graduates. Producing highly competitive graduates ready to compete requires lecturers with strong core competencies and differentiated competencies. In addition to having differentiated competence, lecturers producing high performance require an attitude of engagement towards work and the organization